Functional characterization of the Human Copper Transporters hCTR1 and hCTR2 in the yeast Saccharomyces cerevisiae - Barata-Antunes, Cláudia (2018)
Copper (Cu) is an essential trace element for both eukaryotic and prokaryotic organisms. It plays a crucial role as co-factor of metalloenzymes that participate in important cellular processes, such as growth, development and physiology. Although its importance in maintaining cell health, high level of this ion is extremely toxic (Wang et al., 2011). Therefore, cells possess tight regulated systems to conserve copper homeostasis. One of these mechanisms includes the endocytosis of the Copper Transporter 1 (Ctr1) at high Cu levels, a process already verified in yeast and human cells (Liu et al., 2007; Maryon et al., 2013). Besides these new advances, the molecular mechanisms that are behind the intracellular trafficking of the hCtr1 protein are still poor understood. So, to get new insights into this mechanism, an heterologous expression system was created using the yeast Saccharomyces cerevisiae as host (Pereira et al., 2016)). Human CTR1 and CTR2 genes tagged with GFP were cloned into pYPKpw plasmid and transformed into a S. cerevisiae strain disrupted for copper transporters. Importantly, phenotypic assays demonstrated that human Ctr1 complemented the yeast ctr-mutant strain for the ability to grow in a medium containing nonfermentable carbon sources. Moreover, hCtr1 and hCtr2 were localized at the plasma membrane and intracellularly. Data will be presented regarding the expression of hCTRs in different conditions